Exploring Sustainable Financial Behavior Among Millennial Mothers Through an ESG Perspective - Ghalih Sabda Bekti; Ayu Puspitasari; Elok Heniwati (ARBITRASE: Journal of Economics and Accounting, 2026)
This study explores the sustainable financial behavior of millennial mothers and its contribution to family financial resilience from an ESG perspective. Using a qualitative exploratory approach, the study involved 14 millennial mothers selected through purposive sampling from each regency and city in West Kalimantan, Indonesia. Data were collected through semi-structured interviews and analyzed using thematic analysis supported by NVivo. The findings reveal that participants practiced sustainable financial behavior by prioritizing essential household needs, maintaining financial records and budgets, saving for emergencies and children’s education, and exercising responsible consumption. These practices enhanced family financial resilience by improving financial preparedness, managing unexpected expenses, and supporting long-term economic stability. From an ESG perspective, environmental responsibility was reflected in reducing plastic waste, reusing household materials, and adopting environmentally conscious consumption. Social responsibility was demonstrated through prioritizing family wellbeing, children’s education, and healthcare protection, while governance practices included transparent financial management, joint financial decision-making with spouses, and disciplined financial planning. This study highlights how integrating ESG values into household financial practices contributes to resilient and sustainable family welfare amid economic uncertainty. This study contributes to the sustainable finance literature by extending the application of the ESG perspective from corporate and investment contexts to household financial behavior while providing qualitative insights into how millennial mothers integrate sustainability values into everyday financial decision-making.